The Influence of Foundation Policies on Teacher Performance and Teacher Wellbeing at PKBM Alam Purwokerto - Syahputra, Muhammad Yunus (Sean Institute, 2025)
This study aims to analyze the influence of foundation policies on teacher performance and teacher wellbeing at the Purwokerto Alam Community Learning Center (PKBM). The background of this study is based on the importance of the role of institutional policies in creating a work climate that supports the quality of performance and welfare of educators, especially in non-formal educational institutions. This study uses an associative quantitative approach with a population study technique because the number of respondents is limited, namely 20 people consisting of teachers, education personnel, and foundation administrators. Data were collected through a closed questionnaire based on a Likert scale containing indicators of foundation policies, teacher performance, and teacher wellbeing. The instruments were tested for validity and reliability before being subjected to simple linear regression analysis. The results of the validity test showed that all instrument items had a significant correlation with the total score (r count > r table), while the reliability of the instrument reached a Cronbach's Alpha value of 0.805, indicating that the instrument had high internal consistency. Regression analysis showed that the foundation's policy had a significant effect on teacher performance (R² = 0.426; p = 0.002) and teacher wellbeing (R² = 0.503; p = 0.000). The positive regression coefficient value indicated that the better the perception of the foundation's policy, the higher the teacher's performance and wellbeing. These findings indicate that transparent, fair, and supportive foundation policies can create a positive working environment for teachers. Therefore, strengthening institutional policies is a strategic step in managing human resources in non-formal educational institutions such as PKBM.